The Edinburgh companion to Charles Dickens and the arts - John, Juliet 1967-; Wood, Claire 1984- (Edinburgh Companions to Literature and the Humanities, 2024)
Re-examines Charles Dickens's under-recognised importance to nineteenth-century and contemporary understandings of the artsA major reconsideration of Dickens's career and cultural significance and of the idea of 'the arts'Explores a broad engagement with the arts, which locates Dickens in new and surprising contexts - including rap, music, dance, architecture and world cinemaProvides innovative perspectives on questions of cultural hierarchy, artistic production, adaptation, reception, circulation and legacyThe Edinburgh Companion to Charles Dickens and the Arts explores Dickens's rich and complex relationships with a myriad of art forms and the far-reaching resonance of his works across the arts overall. This volume reassesses Dickens's prescient philosophy of art, both through a historical and a present-day lens and in the context of debates about the cultural value of the arts. Across thirty-three original essays, it outlines the ways in which Dickens broke down oppositions between high and low art, money and the aesthetic, the extraordinary and the ordinary, and art for its own sake and the social good. In doing so, it considers how Dickens prefigured the arts of the future, including rap music, television, fanfiction and global cinema